2016
DOI: 10.1002/14651858.cd004073.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin supplementation for preventing miscarriage

Abstract: Taking any vitamin supplements prior to pregnancy or in early pregnancy does not prevent women experiencing miscarriage. However, evidence showed that women receiving multivitamins plus iron and folic acid had reduced risk for stillbirth. There is insufficient evidence to examine the effects of different combinations of vitamins on miscarriage and miscarriage-related outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 216 publications
(12 reference statements)
2
45
0
5
Order By: Relevance
“…Such findings substantiate the provocative contention that VitE also is a nutrient of similar status and significance, both for the fetal brain and for long-term cognitive function, and provide evidence to encourage future reevaluation of recommended VitE intake levels to promote optimal neurodevelopment and cognitive health in humans. Currently, there is only limited information available on the role of VitE in miscarriage [2,65] and cognitive function [66,67] in humans. Clearly, more research is needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings substantiate the provocative contention that VitE also is a nutrient of similar status and significance, both for the fetal brain and for long-term cognitive function, and provide evidence to encourage future reevaluation of recommended VitE intake levels to promote optimal neurodevelopment and cognitive health in humans. Currently, there is only limited information available on the role of VitE in miscarriage [2,65] and cognitive function [66,67] in humans. Clearly, more research is needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Another review demonstrated that the risk of pre-eclampsia, low birthweight, and preterm birth may be reduced by vitamin D supplementation during pregnancy [14]. Evidence also exists that links multivitamin supplementation with iron and folic acid to reduce the risk of miscarriage [15].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to address potential individual micronutrient deficiencies, many women take complex pregnancy multivitamins. Despite high‐frequency use and widespread marketing and promotion, there is a lack of evidence that routine supplementation with multivitamins or supplements containing multiple micronutrients either in pre‐ or periconception is beneficial to pregnancy outcome . In many cases, supplementation with such multivitamins may provide amounts of various vitamins and minerals above what is actually needed.…”
Section: Use Of Multivitaminsmentioning
confidence: 99%